Kewajiban Laki-Laki dan Perempuan Dalam Rumah Tangga - Madsuri (STIT Muslim Asia Afrika, 2021)
Although men and women both have rights and obligations, but in domestic life, both have different roles. Men and women perform their duties and roles according to their respective natures. Men and women are like day and night. Day is a time to work outside the house and the night is a time to rest at home. Of course this does not mean that men are not in the house and women can not leave the house, as long as it is always remembered there is a difference of orientation between men and women. It is impossible for day to precede night and night precede day, each rotating according to its circular line. Men have their own duties as well as women. Women serve as a nursery for the continuation of human life. She conceived, gave birth, breastfed, cared for and educated her children. Indeed, if observed the character and nature of men is different from women. The man is firm and firm in his opinions and actions and he uses the mind more than women. Women are more sensitive to their feelings. Women's main task is to require more feelings than considerations of reason.